The Problem of Medium Specificity in European Theoretical Art History of the Second Half of the 20th Century - Khmelev, Roman A. (Actual Problems of Theory and History of Art, 2022)
In this work, the author focuses on the analysis of methodologies in which the problem of medium specificity appears, and the identification of aspects of the theory in them, aimed at the analysis and interpretation of the components specific for painting, which located both in material planes and in various symbolic spaces. The first part of the study is devoted to the analysis of the problem of the medium specificity in the studies of K. Greenberg. The author traces how arguments in favor of medium specificity are formed in the works of an American art critic, as well as a special attitude towards paintings. Increased attention has been paid to those aspects of Greenberg’s theory that are aimed at the analyzing painting through the material features of the medium. The second part of the work examines the key features of the theory of H. Damisch and N. Bryson. One of the common features of the studies of French theorist and Anglo-American researcher is the increased attention to material traces and marks on the surface of the work, which in semiotic theory are “index”. This approach contributes to the formation of a methodology that is based on the medium specificity of the work, on the one hand, and, on the other, is not limited to the analysis of only the formalistic aspect. This method can be the most productive in relation to the painting of the late 20th — early 21st centuries, which can be based on both modernism attitude and a moment of its rethinking or negation.